Personality Profile and Clinical Correlates of Patients With Substance Use Disorder With and Without Comorbid Depression Under Treatment - Marquez-Arrico, Julia Elena; Río-Martínez, Laura; Navarro, José Francisco; Prat, Gemma; Adan, Ana (Frontiers in Psychiatry, 2019)
Background: Among patients with substance use disorder (SUD), major depressive disorder (MDD) is highly prevalent. Even though, personality plays an important role in treatment outcomes for individuals with SUD and SUD + MDD, few studies have explored personality characteristics in these samples. This study aims to describe personality for patients with SUD taking into account the comorbid MDD, using the Alternative Five Factor Model (AFFM). We also aim to compare SUD + MDD patients with population norms and to elucidate possible personality clinical correlates. Methods: For our study, 116 male patients undergoing for SUD treatment were divided in two groups: SUD only (N = 58) and SUD + MDD (N = 58). To examine personality, we used the Zuckerman-Kuhlman Personality Questionnaire and multiple analyses of covariance were performed to identify differences. In a first analysis, age was introduced as a covariate whereas in a second analysis the continuous variables that showed to have a discriminant value for the groups were added as covariates. Variables predicting the presence of dual diagnosis and personality clinical correlates were analyzed by logistic and linear regression models, respectively. We observed that patients with SUD + MDD show distinctive personality characteristics compared with patients with SUD only and population norms. Results: According to the AFFM, SUD + MDD patients are characterized by higher Neuroticism-Anxiety (positively associated to depressive symptoms) and Impulsivity; and by lower Parties and Friends. Moreover, the probability of having a dual depressive disorder was represented by the amount of medications and substances used. The preference for hard work and the energy self-reported levels (Work Activity trait) are linked to these clinical variables rather than to the presence/absence of a dual depressive disorder. Conclusions: Even when controlling clinical variables related to a higher probability of having a dual depressive disorder, the Neuroticism-Anxiety is a personality trait that strongly differentiates between SUD only and SUD + MDD patients. Further investigation is needed to explore the role of this personality trait as endophenotype in dual depressive men. Our results underline the importance of a dimensional understanding of personality and its clinical correlates among patients with SUD + MDD; this approach could provide us information on specific treatment strategies to improve the prognosis of patients.